ENKRIPSI DATA MENGGUNAKAN ADVANCED ENCRYPTION STANDART 256 - Yudi Wiharto; Ari Irawan (Sekolah Tinggi Teknik - PLN, 2018)
Cryptography is important in securing data and information. Confidential, important information may not be publicly or otherwise protected. It is not impossible for anyone to see, damage, steal or misuse important data from an agency or company through a computer network. The solution is with cryptography or a method of data security that can maintain the confidentiality and authenticity of a data or information. This method is intended for confidential information when sent through network access, such as LAN or internet, cannot be utilized by unauthorized parties. Cryptography supports the aspect of information security, namely protection of confidentiality. Therefore the need to maintain the confidentiality of data and information is a cryptographic application. The process in the form of encryption and decryption used by the user to secure the data without changing the contents of the data. This application has a 32-character key but in its use is made into 2 keys, namely public and private key where the public key is the key filled by the user in accordance with the desire, while the private key is the default key entered by the application at random to meet the length of 32 characters. The AES algorithm used is the AES256 algorithm where this algorithm uses the principle with the number of rounds by key.